How Green Marketing Influences Green Purchase Intention: The Mediating Effect of Green Trust in Avoskin Beauty Consumers in Indonesia - Nur Aulia Rahmah; Annisa Wahyuni Arsyad (Universitas Ibn Khladun Bogor, 2026)
Growing public awareness of global issues has prompted skincare companies in Indonesia to adopt green marketing strategies in their business processes in order to attract consumers. However, the effectiveness associated with green marketingin increasing The extent to which consumers intend to purchase green products is determined by consumer trust in the environmental commitments made by companies. This study aims to examine the effectiveness of Avoskin’s green marketing in determining green purchase intention, with green trust acting as a mediating factor. This research adopted a quantitative survey approach to collect and analyze the data involving the distribution of questionnaires to respondents. The study was conducted amongst 150 Avoskin users in Indonesia aged between under 20 and 30 years. Non-probability sampling was employed, specifically using purposive sampling. The data were analysed using Smart PLS-3 through outer model, inner model and bootstrapping tests. The results of this study indicate a significant the findings indicate thatgreen marketing and green trust on green purchase intention, In addition, significant mediating effect of green trust on green purchase intention.